Declining laser peripheral iridotomy for angle closure alongside rising cataract surgeries: A nationwide cohort study in South Korea - WooJin Kim; Chan Mi Park; Seokjin Kong; Dong Hyun Kim; Youngsub Eom; Jong Suk Song (PLoS ONE, 2026)
Purpose To examine recent nationwide trends in cataract surgeries and laser peripheral iridotomy (LPI) in Korea, and to assess their temporal association and patient-level characteristics influencing procedure patterns. Methods This retrospective cohort study used data from the Korean National Health Information Database. Individuals aged 65 years and older who underwent cataract surgery or LPI between 2016 and 2021 were analyzed. Primary outcomes included the annual volumes of cataract surgeries and LPIs, their temporal association, patient demographics, the proportion of LPI patients subsequently undergoing cataract surgery, and the interval to surgery. Results Cataract surgeries increased annually until 2019, declined in 2020, and rose again in 2021, whereas LPI procedures steadily decreased after 2017. A negative correlation was observed between annual cataract surgeries and LPIs ( r = −0.657, P = 0.156), although not statistically significant. Among patients aged 65–74 years, the correlation was significant ( r = −0.943, P = 0.005). Among those who underwent LPI, 92.1% subsequently received cataract surgery, with a median interval of 121 days between procedures. Conclusion This nationwide study demonstrated a temporal association and demographic characteristics underlying the recent increase in cataract surgeries and the concurrent decline in LPI procedures in Korea. Notably, most patients who underwent LPI subsequently received cataract surgery within a relatively short interval, suggesting a possible clinical shift toward earlier lens extraction in the management of angle closure.